Development of muscle strength in relation to training level and testosterone in young male soccer players - Hansen, L.; Bangsbo, J.; Twisk, J.; Klausen, K. (Journal of Applied Physiology, 1999)
Isometric and functional strength of ninety-eight 11-yr-old male soccer players at an elite (E) and nonelite (NE) level were determined (3-4 times) through a 2-yr period, and the changes were related to growth and maturation. The initial isometric strength for extension with dominant leg [1,502 +/- 35 (E) vs. 1,309 +/- 39 (NE) N], extension with nondominant leg (1,438 +/- 37 vs. 1,267 +/- 45 N), extension with both legs (2,113 +/- 76 vs. 1,915 +/- 72 N), back muscles (487 +/- 11 vs. 414 +/- 10 N), abdominal muscles (320 +/- 9 vs. 294 +/- 8 N), and handgrip (304 +/- 10 vs. 259 +/- 8 N) increased by 15-40% during the period. Broad jump increased (P < 0. 05) by 15 (E) and 10% (NE). The E players had higher (P < 0.05) initial isometric strength and broad jump performance compared with NE players, and differences were maintained throughout the period (multiple ANOVA for repeated measures) also when adjustment was made for age, dimensions, testosterone, and insulin-like growth factor I (generalized estimating equations analyses). The development of strength for both E and NE players together was significantly (P < 0. 001) related to changes in serum testosterone concentrations. The present data indicate that testosterone is important for development of strength in young boys and that, independent of serum testosterone concentration, E players have developed greater muscle strength compared with NE players.